Histone demethylase UTX is a therapeutic target for diabetic kidney disease - Chen, Hong (J Physiol, 2018)
KEY POINTS: Diabetic kidney disease (DKD) is a major complication of diabetes. We found that UTX (ubiquitously transcribed tetratricopeptide repeat on chromosome X, also known as KDM6A), a histone demethylase, was upregulated in the renal mesangial and tubular cells of diabetic mice and DKD patients. In cultured renal mesangial and tubular cells, UTX overexpression promoted palmitic acid‐induced elevation of inflammation and DNA damage, whereas UTX knockdown or GSK‐J4 treatment showed the opposite effects. We found that UTX demethylase activity‐dependently regulated the transcription of inflammatory genes and apoptosis; moreover, UTX bound with p53 and p53‐dependently exacerbated DNA damage. Administration of GSK‐J4, an H3K27 demethylase inhibitor, ameliorated the diabetes‐induced renal abnormalities in db/db mice, an animal model of type 2 diabetes. These results revealed the possible mechanisms underlying the regulation of histone methylation in DKD and suggest UTX as a potential therapeutic target for DKD. ABSTRACT: Diabetic kidney disease (DKD) is a microvascular complication of diabetes and the leading cause of end‐stage kidney disease worldwide without effective therapy available. UTX (ubiquitously transcribed tetratricopeptide repeat on chromosome X, also known as KDM6A), a histone demethylase that removes the di‐ and tri‐methyl groups from histone H3K27, plays important biological roles in gene activation, cell fate control and life span regulation in Caenorhabditis elegans. In the present study, we report upregulated UTX in the kidneys of diabetic mice and DKD patients. Administration of GSK‐J4, an H3K27 demethylase inhibitor, ameliorated the diabetes‐induced renal dysfunction, abnormal morphology, inflammation, apoptosis and DNA damage in db/db mice, comprising an animal model of type 2 diabetes. In cultured renal mesanglial and tubular cells, UTX overexpression promoted palmitic acid induced elevation of inflammation and DNA damage, whereas UTX knockdown or GSK‐J4 treatment showed the opposite effects. Mechanistically, we found that UTX demethylase activity‐dependently regulated the transcription of inflammatory genes; moreover, UTX bound with p53 and p53‐dependently exacerbated DNA damage. Collectively, our results suggest UTX as a potential therapeutic target for DKD.